A Composite Nanomaterial with the Ability to Regulate Oxidative Stress and Anti‐inflammatory for the Treatment of Osteoarthritis. Issue 17 (2nd May 2022) - Wang, Yi; Deng, Qiuping; Zheng, Qinghua; Li, Ruyan; Liu, Baoqing; Mo, Xiaoli; Zhou, Jiahong; Shen, Jian
Abstract: The current pharmacologic treatment of osteoarthritis (OA) is limited to pain relief medications that may bring obvious side effects, so new treatment ideas need to be proposed. Eliminating excess reactive oxygen species (ROS) and maintaining the anabolic and catabolic function of chondrocytes may provide a new strategy for OA treatment. Here, we prepared nanoparticles (m@PDA−Q) composed of polydopamine (PDA), quercetin and modified hyaluronic acid. PDA not only functions as a carrier for hydrophobic drugs, but also as a certain ROS scavenger. On this basis, hyaluronic acid was modified and cross‐linked under ultraviolet light so it could polymerize on the surface of nanoparticles and provide protection and lubrication to the joints. Relevant experiments showed good biocompatibility of the composite nanomaterials that we synthesized. Its function in regulating the antioxidant defense system, anti‐inflammatory and regulating the anabolism and catabolism of chondrocytes was also confirmed. The m@PDA−Q nanoparticle is expected to become a representative drug candidate for the treatment of OA. Abstract : The polydopamine loaded with quercetin is wrapped with hyaluronic acid cross‐linked by ultraviolet light. This composite nanomaterial can effectively control inflammation‐mediated apoptosis of chondrocytes, remove ROS, and maintain the balance of catabolism and anabolism.